Factors demotivating students to participate in English speaking lessons at Viet-Hung Industrial University . M.A Thesis Linguistic - Nguyễn, Thị Hương (University of Languages and International Studies, 2017)
The topic of the thesis is resulted from what several teachers at Viet-Hung Industrial University have generally said about the poor performance of students of the University in speaking. There seems to be a lack of interest or motivation among them to par (...)